MODEL KEPEMIMPINAN DAN SUASANA AKADEMIK DALAM PEMBELAJARAN SEJARAH SMA DI KOTA SEMARANG - Utomo, Cahyo Budi (Paramita: Historical Studies Journal, 2012)
This study develop a model of leadership and academic atmosphere in high school history teaching in the city of Semarang. The data obtained from field studies using a Likert scale questionnaire that was developed from theoretical constructs and indicators. Data analysis conducted by the SmartPLS program. Modeling results indicate that some of the constructs of transformational leadership has not developed fully understood by the teacher of history, especially in the construct of simplification, facilitation, and commitment. Furthermore, an alternative model was developed to see another positive trend in order to find a better model fit. The results of the analysis of alternative models tested had a composite reliability values ​​greater than 0.80 (T count > 1.99 at 0.05 significance level) so that it can be concluded that the model has good reliability. In contrast, the contribution of aspects of leadership to the academic atmosphere is relatively small and likely not significant due to poor understanding of the respondents so that should be given training for teachers related to this aspect of transformational leadership.Keywords: leadership, transformational, academic atmosphere, teaching high school historyPenelitian ini bertujuan untuk mengembangkan model kepemimpinan dan suasana akademik dalam pembelajaran sejarah SMA di kota Semarang. Data didapatkan dari studi lapangan menggunakan angket skala Likert yang dikembangkan dari konstruk dan indikator teoretis. Analisis data menggunakan program SmartPLS. Hasil pemodelan menunjukkan beberapa konstruk yang dikembangkan dari kepemimpinan transformasional belum dipahami sepenuhnya oleh guru sejarah, utamanya pada konstruk simplifikasi, fasilitasi, dan komitmen. Lebih lanjut, model alternatif dikembangkan untuk melihat kecenderungan lain yang positif dalam rangka mencari model yang lebih fit. Hasil analisis model alternatif yang diuji memiliki nilai komposit reliabilitas lebih besar dari 0,80 (T hitung > 1,99 pada taraf signifikansi 0,05) sehingga dapat disimpulkan model memiliki reliabilitas yang baik. Sebaliknya, kontribusi aspek kepemimpinan terhadap suasana akademik relatif kecil dan cenderung tidak signifikan karena pemahaman responden yang kurang baik sehingga perlu diberikan pelatihan bagi guru terkait aspek kepemimpinan transformasional ini.Kata Kunci: kepemimpinan, transformasional, suasana akademik, pembelajaran sejarah